Pengaruh Environmental Social dan Governance Disclosure Terhadap Financial Distress - Syahila Almuna Yulianda; Ambar Woro Hastuti (PT. Intelek Cendikiawan Nusantara, 2026)
Financial distress in companies is a serious concern for management and other stakeholders in decision-making. Financial distress can be influenced by both financial and non-financial factors. In the development of modern business practices, attention to non-financial factors is increasing, one of which is through the concept of Environmental, Social, and Governance (ESG). This study aims to analyze the influence of ESG disclosure on financial distress. Financial distress is measured using the Altman Z-Score model, while ESG disclosure is measured using Global Reporting Initiative (GRI) Standards indicators. Infrastructure sector companies were selected as research objects because they require extensive land acquisition, which certainly impacts the lives of surrounding communities. The research sample was taken using the purposeful sampling method, resulting in 15 companies, with an observation period of 2022-2024, resulting in 45 observational data sets. Environmental and social disclosure aspects were measured based on the GRI 300 and 400 series, while governance disclosure aspects were measured based on GRI 2 (General Disclosures). The data analysis technique used multiple linear regression analysis. The results of the study indicate that Environmental and Social Disclosure influence financial distress, while Governance Disclosure does not. However, overall, these three aspects of ESG disclosure are not fully able to explain financial distress, as indicated by an Adjusted R Square value of 13.2%. The remaining 86.8% is influenced by other variables outside the research model. This indicates that there are still other dominant factors causing companies to experience financial distress